Solution‐processed lead iodide for ultrafast all‐optical switching of terahertz photonic devices - Manjappa, Manukumara (2020)
Solution‐processed lead iodide (PbI2) governs the charge transport characteristics in the hybrid metal halide perovskites. Besides being a precursor in enhancing the performance of perovskite solar cells, PbI2 alone offers remarkable optical and ultrasensitive photoresponsive properties that remain largely unexplored. Here, the photophysics and the ultrafast carrier dynamics of the solution processed PbI2 thin film is probed experimentally. A PbI2 integrated metamaterial photonic device with switchable picosecond time response at extremely low photoexcitation fluences is demonstrated. Further, findings show strongly confined terahertz field induced tailoring of sensitivity and switching time of the metamaterial resonances for different thicknesses of PbI2 thin film. The approach has two far reaching consequences: the first lead‐iodide‐based ultrafast photonic device and resonantly confined electromagnetic field tailored transient nonequilibrium dynamics of PbI2 which could also be applied to a broad range of semiconductors for designing on‐chip, ultrafast, all‐optical switchable photonic devices.